MENINGKATKAN MOTORIK KASAR MELALUI PAPAN TITIAN BAGI ANAK CEREBRAL PALSY KELAS I DI SLB LUBUK KILANGAN PADANG - Ghina Sausan (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract :Motor development is the growth process of a child's motor skills. Basically, these developments evolve in line with less maturity of the nerves and muscles of children. Thus, any simple movement of any kind, is the result of a complex interaction patterns of the various parts and systems in the body that is controlled by the brain.Starting from the observation that the researchers found when observation of cerebral palsy children have not been able through a rough phase motor phase is running straight ahead, until the observation after the treatment given to the target behavior gross motor skills. The purpose of this study prove plank can improve gross motor skills in children cerebral palsy spastic type. This research uses experimental approach in the form of single subject research (SSR) with multiple baseline design cross variables and data analysis using the technique of visual analysis chart.Analysis of the data shows that the first baseline before the given intervention conducted for 6 days with a mean level of 6.7 and a tendency toward increased slightly intervention continued for 12 days with a mean level of 3.58, a tendency towards increasing and improving data changes (+). Furthermore, a second baseline condition after the intervention for 8 days with a tendency toward increased (+). The target behavior has a data overlape 0%. It was concluded that the plank can improve gross motor skills for the type of spastic cerebral palsy children. Based on the results of this study should teachers create new learning strategies to train the child's gross motor skills for the type of spastic cerebral palsy. Kata Kunci : Papan Titian; Keseimbangan Berjalan; Anak Cerebral Palsy